Systematics of the Third Row Transition Metal Melting: The HCP Metals Rhenium and Osmium - Leonid Burakovsky; Naftali Burakovsky; Dean Preston; Sergei Simak (Crystals, 2018)
The melting curves of rhenium and osmium to megabar pressures are obtained from an extensive suite of ab initio quantum molecular dynamics (QMD) simulations using the Z method. In addition, for Re, we combine QMD simulations with total free energy calculations to obtain its phase diagram. Our results indicate that Re, which generally assumes a hexagonal close-packed (hcp) structure, melts from a face-centered cubic (fcc) structure in the pressure range 20–240 GPa. We conclude that the recent DAC data on Re to 50 GPa in fact encompass both the true melting curve and the low-slope hcp-fcc phase boundary above a triple point at (20 GPa, 4240 K). A linear fit to the Re diamond anvil cell (DAC) data then results in a slope that is 2.3 times smaller than that of the actual melting curve. The phase diagram of Re is topologically equivalent to that of Pt calculated by us earlier on. Regularities in the melting curves of Re, Os, and five other 3rd-row transition metals (Ta, W, Ir, Pt, Au) form the 3rd-row transition metal melting systematics. We demonstrate how this systematics can be used to estimate the currently unknown melting curve of the eighth 3rd-row transition metal Hf.